Analysis of Shipbuilding Business Development Strategy in Batang Port with Pest and Five Porter Approach - Danang Satrio; Ari Muhardono; M. Adi Firmansyah (Lafadz Jaya Publisher, 2025)
This research examines the Karangasem shipbuilding business development strategy using the PEST and Five Porter approaches. Policy changes occurred in 2020 during the Covid-19 pandemic. Licensing for ship issuance has stopped so that orders have dropped drastically to the point that several shipyards have reduced the number of workers. Policy changes occurred again in mid-2021 until now, when the legality of ships was transferred from initially to regional government to central government. Entrepreneurs make money by making ships without orders (Idle Stock). Entrepreneurs' expectations that deviate greatly cause businesses to decline further, which has an impact on increasing production costs where additional raw materials are needed, direct labor costs increase and losses from raw materials that are not used increase. This has an impact on decreasing entrepreneurs' income and no returns. This research is descriptive research with a qualitative approach in the form of PEST (Political, Economic, Social & Cultural, Technological) and Five Porter's Diamond analysis. The results of the research show that competition between similar companies means that shipyards are quite strategic in the growth of similar industries each year, product differentiation with competitors is quite high and production costs are quite large, and the threat of new entrants is that shipyards have quite a high threat to government policy and the impact on government.